Analisis Pasal 280 Ayat (1) huruf d Undang-Undang Nomor 1 Tahun 2023 Terhadap Kesesuaian dengan Kebebasan Pers - Agnes Floresta Nugraini Nugroho; Slamet Suhartono (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Freedom of the press is one thing that cannot be reduced in the slightest. The problem is that freedom of the press has the potential to be hampered by the prohibition on publication of the judicial process as regulated in Article 280 Paragraph (1) Letter d of Law Number 1 of 2023. As a result, this article is being questioned as to its compatibility with press freedom. This research aims to determine the suitability of Article 280 of Law Number 1 of 2023 from the perspective of press freedom and legal protection for people/press who are convicted in Article 280 of Law No. 1 of 2023. This type of research is normative with a statutory approach and conceptual. The results of this research are that Article 280 Paragraph (1) Letter d of Law Number 1 of 2023 has the potential to violate openness, access to information and press freedom. However, this prohibition does not mean limiting press freedom because the press can still attend trials, the press can still release post-trial news, and the press is allowed to do live streaming if permitted by the court. Legal protection for journalists or the press applies when the parties concerned carry out their profession but does not apply absolutely. If journalists commit Article 280 of Law Number 1 of 2023, they will still be subject to criminal penalties for violating the law. For these actions, press companies and press organizations must be held responsible by providing legal protection in the form of legal aid and providing assistance and support to journalists who are experiencing criminal threats.